The Relationship Between Pregnant Women's Participation in Pregnant Women's Classes and Integrated ANC (Ante Natal Care) With The Incidence of Stunting in Toddlers in The Work Area of Pesantren I Public Health Center Kediri City - Santoso, Chandra Agustin; M. Ali Sodik (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2025)
Stunting is a problem currently being faced in Indonesia. Toddlers with stunting problems show poor linear growth. This is because toddlerhood is a golden period in growth and development, and affects physical and mental development. Efforts to deal with stunting are prioritized in prevention, one of which is through Integrated ANC (Ante Natal Care) and Pregnant Women's Classes. The research design used was observational with a cross-sectional approach. The population in this study was 1296 toddlers using the Proportion to size sampling technique, a sample of 301 Posyandu was obtained. The statistical analysis used was the Chi Square Spearman Correlation statistical test. Based on the results of this study, it is known that the participation of pregnant women in the Pregnant Women's Class at the Pesantren 1 Health Center in Kediri City was mostly active, namely 250 people (81.7%). The participation of pregnant women in integrated ANC (Ante Natal Care) at the Pesantren 1 Health Center in Kediri City was mostly active, namely 292 people (95.4%). The results of the Spearman Correlation analysis of Stunting incidents in toddlers showed that from the independent variables, namely the participation of pregnant women in the pregnant women's class, the strongest correlation was with the incidence of stunting at the Pesantren 1 Health Center in Kediri City. Improving the implementation of the pregnant women's Class and integrated ANC activities for Pregnant Women in order to prevent stunting.